Learning action cell as an in-house professional development training - Vega, Mark Gil A.; Orleans, Antriman V. (Intelektual Pustaka Media Utama, 2025)
Learning action cell (LAC) sessions are structured professional development activities tailored for schools to enhance pedagogical skills, teaching methodologies, and assessment methods to improve student academic achievement. This study investigated the implementation of the LAC as an internal development training program for science teachers in remote regions of the Philippines. A total of 403 science educators participated in the study to collect implementation strategies seen in the LAC. The science teachers’ experiences in the LAC implementation were assessed using a survey questionnaire and a case study through focus group discussions (FGD). Based on the findings, LAC enhances educators’ perceptions of professional development training. As a professional development tool, the LAC helped science teachers develop students’ science holistic development, technology innovation, and cultural knowledge. The idea creates a community of scientific educators who collaborate to improve their facilitation, innovation, and research skills, promoting professional leadership and competency in the field. Consequently, the efficacy of LAC necessitates high-quality training aimed at specific objectives. Science educators acknowledged that LAC enhances instructional leadership and pedagogical proficiency.